1988
DOI: 10.1056/nejm198802043180501
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Transluminal Coronary Angioplasty in 1985–1986 and 1977–1981

Abstract: In August 1985, the Percutaneous Transluminal Coronary Angioplasty Registry of the National Heart, Lung, and Blood Institute reopened at its previous sites to document changes in angioplasty strategy and outcome. The new registry entered 1802 consecutive patients who had not had a myocardial infarction in the 10 days before angioplasty. Patient selection, technical outcome, and short-term major complications were compared with those of the 1977 to 1981 registry cohort. The new-registry patients were older and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
11

Year Published

1988
1988
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 762 publications
(77 citation statements)
references
References 10 publications
1
65
0
11
Order By: Relevance
“…1 In 2 large series reported by the National Heart, Lung and Blood Institute, emergency CABG was required in 6% of the cases between 1977 and 1981 and in 3% between 1985 and 1986. 10 There has been an additional decline in the reported prevalence of emergency CABG in the 1990s. In a study of 5655 patients undergoing PCIs by Shubrooks et al, 11 emergency CABG was required in 2.2% of the cases in 1992 to 1993 and 0.6% of the cases in 1997.…”
Section: Discussionmentioning
confidence: 99%
“…1 In 2 large series reported by the National Heart, Lung and Blood Institute, emergency CABG was required in 6% of the cases between 1977 and 1981 and in 3% between 1985 and 1986. 10 There has been an additional decline in the reported prevalence of emergency CABG in the 1990s. In a study of 5655 patients undergoing PCIs by Shubrooks et al, 11 emergency CABG was required in 2.2% of the cases in 1992 to 1993 and 0.6% of the cases in 1997.…”
Section: Discussionmentioning
confidence: 99%
“…In the first NHLBIsponsored PTCA registry, 9% of patients had diabetes mellitus 13 ; in the second registry, this proportion had risen to 12%, 3 and in the Bypass Angioplasty Revascularization Investigation, 19% of patients were diabetic. 2 In contrast, 23% of patients in EPILOG had diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, Ϸ25% of all patients who undergo PTCA are smokers. 7,8 Several studies have shown that long-term risks of myocardial infarction and death are higher for smokers than for nonsmokers after both percutaneous 8 and surgical coronary revascularization. 9 -11 Moreover, smoking is associated with microvascular endothelial dysfunction that may limit the ability of epicardial revascularization to restore normal coronary blood flow.…”
Section: See P 1340mentioning
confidence: 99%